Development Status of Compressor Technology for Medium and Large Capacity Industrial High-temperature Heat Pumps - 马凯; 陈文卿; 李丹童; 何志龙; 邢子文 (Zhileng xuebao)
Heat pump technology is an energy-saving technology that can effectively combat global warming and reduce carbon emissions. Industrial heat pumps recover waste heat from the heating process, heat water or air, and reduce electricity consumption and carbon emissions. Industrial heat pumps are energy-saving, environmentally friendly, and provide stable heating. They have been widely used in all stages of production and life. This article analyzes the compressor types and characteristics of domestic and foreign industrial waste heat high-temperature heat pumps. Focusing on medium and large capacity twin-screw compressors and centrifugal compressors, the research status is analyzed, and the possible development direction of medium and large capacity high-temperature heat pumps is given.